THE ROLE OF SOCIAL TOURISM IN BOOSTING ECONOMIC ACTIVITY, BASED ON SPANISH SOCIAL POLICY PROGRAMES IN SPAIN - Górska, Ewa (Acta Scientiarum Polonorum. Oeconomia, 2010)
The main objective of this paper is to show the importance of social tourism as a commitment to fight de-seasonalisation of tourism activity and unemployment. The article attempts to analyze social policy programs supported by the Spanish government (Program of Holidays for Elderly – Vacaciones para Mayores) and its role in boosting economic activity. Holidays Program for Elderly in Spain has historically pursued two essential objectives: to improve the quality of life of elderly people and to encourage the creation and maintenance of employment in tourism industry in times of low activity. Spanish government yearly invests in the program around 50 million euro, and every year the program generates savings in payments for unemployment and income via taxes and fees (VAT, income taxes, social security taxes, excise duties, etc). Holiday Program for Elderly in Spain is one of the most interesting solutions in social tourism and in 2009 it has been recognized by European Commission as the example of good practices in field of social tourism.